THE EFFECTIVENESS OF FLEXIBILITY, ORGANIZATIONAL CULTURE, COMPETENCE AND INTEGRITY TO IMPROVING APIP PERFORMANCE, KLATEN DISTRICT - Budi Prestyo; Istiatin Istiatin; Sudarwati Sudarwati (PERCIPIENCE International Journal of Social, Administration, & Entrepreneurship, 2022)
The purpose of this study was to determine the effect of the effectiveness of flexibility, organizational culture, competence and integrity on improving APIP performance at the Klaten Regency Inspectorate. The type of data in this study is quantitative data. Sources of data used in this study derived from primary data, namely questionnaires distributed to employees of the Klaten Regency Inspectorate with 54 employees. The sampling technique is a saturated sampling technique. The test of this research instrument uses validity and reliability tests. Data analysis using multiple linear regression, model feasibility test, hypothesis testing, and the coefficient of determination of the model using SPSS. The results showed that the F test results showed that flexibility, organizational culture, competence and integrity simultaneously and significantly affected APIP's performance at the Klaten Regency Inspectorate. Based on the t-test, the flexibility and competence variables have no and no significant effect on the performance of APIP in Klaten Regency, while the organizational culture and integrity variables have a positive and significant effect on the performance of APIP in Klaten Regency.